Photovoltaic Remote Data Transmission Based on Bigdata Platform and its Application - HAO Bo; DING Congcong; CHENG Pei (Kongzhi Yu Xinxi Jishu)
With the rapid development of new energy industry, large-scale photovoltaic products are put into operation and the traditional photovoltaic industry equipment operation status monitoring method cannot meet the requirements of product real-time data mass storage, high-concurrent access to high-volume equipment, real-time processing etc. Therefore, a remote data transmission and application scheme based on big data platform was proposed, which ensures data transmission on the basis of safety. The data of PV products will be summarized to the big data platform and the application system will be developed based on the massive photovoltaic product data. The application system developed by using virtual private network as transmission channel and high availability, high concurrency and big storage server cluster as storage and processing equipment can greatly enhance the user experience and meet the needs of users.